A transgenic mouse line for rabies virus-mediated trans-synaptic tracing in the postnatal developing brain. - Kengo Inada; Mitsue Hagihara; Miho Kihara; Takaya Abe; Kazunari Miyamichi (PLoS ONE)
Neural circuits are composed of numerous neurons that perform diverse functions. Understanding the mechanisms of neural processing requires elucidating the connections among individual neurons. Rabies virus (RV)-mediated trans-synaptic tracing enables the visualization of direct presynaptic neurons of a defined neural population, facilitating the precise mapping of neural circuits across various brain regions. This method relies on RV mutants that require the expression of the TVA receptor and rabies glycoprotein to infect and spread to presynaptic neurons. Traditionally, adeno-associated virus (AAV) has been used to express these proteins. However, because AAV requires several weeks to achieve sufficient gene expression, it is challenging to use this approach for studying neural connections during postnatal development. To address this limitation, we generated a transgenic mouse line, termed Ai162-nCTG, which expresses nuclear-localized mCherry, the TVA receptor, and rabies glycoprotein in a Cre-dependent manner. As a proof-of-principle, we crossed the Ai162-nCTG line with the vasopressin-Cre line. In the paraventricular hypothalamic nucleus, where a major cluster of vasopressin neurons exists, mCherry expression was highly specific to vasopressin neurons, although not all vasopressin neurons co-expressed mCherry. We injected RV into the paraventricular hypothalamic nucleus and compared the labeling patterns with those of the conventional AAV-based approach. Although both methods labeled input cells in similar brain regions, the AAV-based approach was superior in terms of labeling efficiency. We also demonstrated that the Ai162-nCTG-based method enables rabies virus-mediated trans-synaptic tracing in mice at postnatal day 7 and 30. The distribution of presynaptic neurons was largely similar in the juvenile and adult stages, suggesting that paraventricular vasopressin neurons do not significantly change their presynaptic inputs during post-weaning development. Taken together, these findings suggest that the Ai162-nCTG line can be used for rabies virus-mediated trans-synaptic tracing when AAV administration is challenging. We also acknowledge and discuss the technical constraints associated with this mouse line.